On the Cauchy- Schwarz Inequality for Vectors in the inner Product spaces with Applications - Allah Elnour, Khalid Abd Elrazig Awad (Journal of natural sciences, life and applied sciences, 2018)
In this paper, eleven different proofs for Cauchy Schwarz inequality are considered on the inner product spaces, and specific teqnique of the inequality was used to establish various proofs of some new related inequalities are obtained, Which contributed to the establishment of different mathematical inequalities, notably the application, which shows multiple relationships on the sides of the triangle.